Volatile β-Ocimene Can Regulate Developmental Performance of Peach Aphid Myzus persicae Through Activation of Defense Responses in Chinese Cabbage Brassica pekinensis - Kang, Zhi-Wei; Liu, Fang-Hua; Zhang, Zhan-Feng; Tian, Hong-Gang; Liu, Tong-Xian (Frontiers in Plant Science, 2018)
In nature, plants have evolved sophisticated defense mechanisms against the attack of pathogens and insect herbivores. Plant volatile-mediated plant-to-plant communication has been assessed in multitrophic systems in different plant species and different pest species. β-ocimene is recognized as an herbivore-induced plant volatile that play an important role in the chemical communication between plants and pests. However, it is still unclear whether β-ocimene can active the defense mechanism of Chinese cabbage Brassica pekinensis against the peach aphid Myzus persicae. In this study, we found that treatment of Chinese cabbage with β-ocimene inhibited the growth of M. persicae in terms of weight gain and reproduction. Moreover, β-ocimene treatment negatively influenced the feeding behavior of M. persicae by shortening the total feeding period and phloem ingestion and increasing the frequency of stylet puncture. When given a choice, winged aphids preferred to settle on healthy Chinese cabbage compared with β-ocimene-treated plants. In addition, performance of the parasitoid Aphidius gifuensis in terms of Y-tube olfaction and landings was better on β-ocimene-treated Chinese cabbage than on healthy plants. Furthermore, β-ocimene significantly increased the expression levels of salicylic acid and jasmonic acid marker genes and the accumulation of glucosinolates. Surprisingly, the transcriptional levels of detoxifying enzymes (CYP6CY3, CYP4, and GST) in aphids reared on β-ocimene-treated Chinese cabbage were significantly higher than those of aphids reared on healthy plants. In summary, our results indicated that β-ocimene can activate the defense response of Chinese cabbage against M. persicae, and that M. persicae can also adjust its detoxifying enzymes machinery to counter the host plant defense reaction.